A model-based simulation approach to support the product configuration and optimization of gas turbine ducts. Issue 6 (2nd November 2018) - Cicconi, Paolo; Raffaeli, Roberto; Marchionne, Matteo; Germani, Michele
ABSTRACT: Nowadays, product configuration and optimization are very important topics in several industrial applications such as the manufacturing of Engineered-to-order (ETO) products, where there is a fierce increase in market competition. The product configuration allows past design solutions to be reused and new product variants to be defined and pre-designed. However, the delivery of new configurations of products requires a technical feasibility analysis before closing the contract of the order with the customer. There is a lack of commercial tools which can support the designer from the early configuration phase to the product optimization with the automatic generation of geometric models and simulations. While traditional software tools can be used for the product configuration, with automation in the CAD modeling, other ones can combine optimization algorithms with numerical simulations. However, the combination of all these design levels requires the development of a dedicated platform tools. The research aims to reduce time and cost related to the early design phase of an oil & gas system, focusing on gas turbine ducts. The paper proposes a methodological approach to integrate the design optimization with the product configuration using Model-Based simulations to verify the technical feasibility and to optimize the product design. As a test case, the early design of a gas turbine chimney is proposed. GRAPHICAL ABSTRACT: